Plant of the month - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
One of the features of MedPlant (see Links, page 10) is the 'plant of the month'. In May 2002 it was Vernonia amygdalina, a bitter leaf shrub indigenous to sub-Saharan Africa. Called mujonso by Tanzanians or Iwuro by Nigerians, it is used to treat...